Profilaxia pós-exposição sexual para hiv: uma análise retrospectiva sobre a adesão e o seguimento das pessoas assistidas - Paulina Horta Liza (2019)
Introduction: The HIV post-exposure prophylaxis (PEP) is part of a multiple-action prevention plan against HIV/AIDS. It is recommended for situations involving failure or the non-use of condoms. In the Brazilian program, this plan involves taking antiretroviral medicines (ART) for 28 days, starting up to 72 hours of potential exposure to HIV, and a three-stage follow-up with the assisted individual. Although this technique is renowned in several countries, studies indicate the need for investment in research that seeks to elucidate factors involved in the adherence to prophylaxis. The use of PEP is still recent and national publications in this area are scarce. Objective: To analyse adherence to prophylaxis and compliance with follow-up stages for the individuals assisted by the Programa Brasileiro de Profilaxia Pós-Exposição sexual ao HIV, as a result of consensual intercourse. Method: Observational study, retrospective, carried out between February 2011 and December 2017, with PEPs dispensed at a reference health centre, which is responsible for the largest number of treatments in the city of Belo Horizonte, Minas Gerais – Brazil. Secondary data collection carried out with a 68-variable instrument. The data was stored in the EPI-3.1 DATE software and analyzed by the statistical software SPSS 21.0. The sample was characterised through frequency calculation, measures of central tendency and variability. To assess the factors associated with adherence to prophylaxis and to the follow-up, the following have been used: the Pearson Chi-square test, the Mann-Whitney test and the binary logistic regression model, with estimates of the Odds Ratio value and confidence interval of 95%. All the analysis considered a significance level of 5%. Results: Out of the 1996-user sample, the majority were men, 30 years old on average, brown-coloured, with a higher education degree, and residents of the city of Belo Horizonte. Exposures were predominantly due to condom breakage or failure (53.8%) arising from anal intercourse (56.3%), intercourse with unknown serology partners, but belonging to the population of high prevalence of HIV (57.4%). More than half of them (68.1%) received the antiretroviral drugs composed of Tenofovir, Lamivudine, Atazanavir and Ritonavir. Side effects were observed in 84.9%. 33.6% adhered to medications for 28 days. In cases of partial adherence, the side effect was the main reason for an interruption for 56.1%. Regarding the follow-up cases, 50.4% returned for at least one of the stages - basal exams (32.0%); 1st HIV test (36.6%) and 2nd test (15.1%). A total of 6.8% have completed all the stages. Higher adherence to PEP was associated with the following factors: advanced age, residence in Belo Horizonte or its metropolitan region, being bisexual, having had intercourse with a partner known to be HIV positive and not taking Tenofovir, Zidovudine and Lamivudine antiretrovirals. The factors associated with the highest chances of follow-up completion were advanced age and having had intercourse with a partner known to be HIV positive and not taking the aforementioned antiretrovirals. There have been two cases of seroconversion to HIV – one of them due to early interruption of the prophylaxis, and the other due to continuing risk exposure. Conclusion: Low rates of adherence to PEP and follow-up procedures were observed, signposting that the effectiveness of this program is dependent on a combination of strategies, based on the predictors of adherence and public measures that respond to the profiles and the specificities of population. Possible solutions involve increased access to treatment, incorporation of communication technologies; the provision of educational material, expansion of treatment centres, choosing better tolerability antiretroviral drugs, campaigns targeting women and younger population, as well as monitoring and offering guidance to assisted individuals. Further research into this area in other treatment centres and regions in Brazil may increase visibility of the Brazilian experience for both the PEP and other combined HIV prevention strategies. Keywords: Post-exposure prophylaxis. HIV. Adherence.